(untitled) (Research, Society and Development, 2022)
The management of water resources has occupied a prominent space in the face of various crises, mainly determined by the scarcity of water. It is known that consumption is prioritized for people, in this development, businesses that are hampered by stoppages, reductions or logistical complications to ensure the quality of life of employees and maintenance of the operation. The objective of this study was to analyze whether this dimension influences companies to invest in the city or not, as a contribution four Constructs are analyzed, being learning that relates to how much people know the water management of the city, the second related to communication, the third, Water Management in the view of the citizens and finally entrepreneurship, how much people are willing to invest in cities with water problems. This study is a survey, carried out with 47 respondents. To collect the information, a questionnaire with 21 questions was applied, being 4 ethnographic and 17 with a Boolean scale, validated by the criteria of the content validity coefficient (CVC). The analysis of results was performed through the application of E Logic and the Kruskal Wallis test to compare whether there is a difference between people residing in central and peripheral regions. The results indicate that the lack of water harms current and future businesses, there is little knowledge about the city’s water planning, there is no articulation between user sectors and public authorities for the use of water and there is a possibility of divestment of business in the city. These factors constitute propositions for water management and as a new dimension for administration, both public and private.